The law of nations and natural law, 1625-1800 - Zurbuchen, Simone (Early modern natural law: studies & sources, 2019)
"The Law of Nations and Natural Law 1625-1800 offers innovative studies on the development of the law of nations after the Peace of Westphalia. This period was decisive for the origin and constitution of the discipline which eventually emancipated itself from natural law and became modern international law. A specialist on the law of nations in the Swiss context and on its major figure, Emer de Vattel, Simone Zurbuchen prompted scholars to explore the law of nations in various European contexts. The volume studies little known literature related to the law of nations as an academic discipline, offers novel interpretations of classics in the field, and deconstructs 'myths' associated with the law of nations in the Enlightenment"--